Individual power settings for subthreshold micropulse laser treatment of chronic central serous chorioretinopathy - Король, Андрій Ростиславович; Задорожний, Олег Сергійович; Кустрин, Тарас Богданович; Насінник, Ілля Олегович; Пасєчнікова, Наталія Володимирівна (My University, 2022)
Purpose: To investigate the efficacy and safety of subthreshold micropulse laser (SML) treatment with individual power settings for chronic central serous chorioretinopathy (CSC). Setting/Venue. The Filatov Institute of Eye Diseases and Tissue Therapy, Odesa, Ukraine Materials and methods: Participants in this prospective, interventional, single-center clinical pilot study included 30 patients (30 eyes) with chronic CSC. The primary objective was decimal best-corrected visual acuity (BCVA). The secondary objectives were the maximal height of subretinal fluid (SRF), central retinal thickness (CRT), number of treatments, and safety from baseline to Months 6. Results: Before treatment mean decimal BCVA was 0.35±0.16, mean CRT was 285±76 µm, and mean baseline maximal height of the SRF ‒ 311±85 µm. Mean decimal BCVA showed significant improvement to 0.45±0.15. Mean CRT decreased significantly to 236±45 µm and 45±25 µm respectively. At Month 6, in 50% (15 eyes) were noted complete SRF resolution. Conclusion: Our study demonstrates the efficacy and safety of subthreshold micropulse laser treatment with individual power settings in patients with chronic CSC. Financial disclosure: no any financial interest.